HD 38858: A solar-Type star with an activity cycle of ∼10.8 yr: Searching for variations in the Balmer and metallic lines - Flores, M. (2018)
Context. The detection of chromospheric activity cycles in solar-Analogue and twin stars can be used to place the solar cycle in a wider context. However, relatively few of these stars with activity cycles have been detected. It is well known that the cores of the Ca II H&K lines are modulated by stellar activity. The behaviour of the Balmer and other optical lines with stellar activity is not yet completely understood. Aims. We search for variations in the Ca II H&K, Balmer, and Fe II lines modulated by stellar activity. In particular, we apply a novel strategy to detect possible shape variations in the Hα line. Methods. We analysed activity signatures in HD 38858 using HARPS and CASLEO spectra obtained between 2003 and 2017. We calculated the Mount Wilson index (SMW), log(R′HK), and the statistical moments of the Ca II H&K, Balmer, and other optical lines. We searched for periodicities using the generalized Lomb-Scargle periodogram. Results. We detect a long-Term activity cycle of 10.8 yr in Ca II H&K and Hα in the solar-Analogue star HD 38858. In contrast, this cycle is marginally detected in the Fe II lines. We also detect a noticeable variation in radial velocity that seems to be produced by stellar activity. Conclusions. HD 38858 is the second solar-Analogue star where we find a clear activity cycle that is replicated in the Balmer lines. Spectral indexes based on the shape of Hα line seem to be more reliable than the fluxes in the same line for detecting activity variations. The cyclic modulation we detected gives place to a variation in radial velocity that previously has been associated with a super-Earth planet. Finally, due to the similarity of HD 38858 with the Sun, we recommend to continue monitoring this star.